Timely And Quality Notification Promotes A Significant Reduction Of Human Satisfactions And Material Damage - Khusanova S.I. (Zien Journals, 2022)
One of the main measures to protect the population from natural and man-made emergencies is the timely notification of the population about the danger that has arisen in the situation in the danger zone, as well as informing about the correct behavior in emergency situations. A very important factor at the initial stage of the development of emergencies is the clear, prompt, concise and informative operation of the local emergency warning system. Timely and high-quality notification contributes to a significant reduction, and sometimes to the complete exclusion of victims and material damage. The article draws attention to the observance of all fire safety measures in educational institutions (particularly in schools) and the timely communication of information about the fire and evacuation of participants in the educational process, observing the identified rational parameters when compiling messages, has a high safety organization efficiency. In other words, the damage from a particular emergency is minimized.
Keywords: emergency; protection of the population; timely notification; communication of information